2017
DOI: 10.1542/peds.2016-4186
|View full text |Cite
|
Sign up to set email alerts
|

The Need to Optimize Adolescent Immunization

Abstract: The adolescent period heralds the pediatric patient's transition into adulthood. It is a time of dynamic development during which effective preventive care measures can promote safe behaviors and the development of lifelong health habits. One of the foundations of preventive adolescent health care is timely vaccination, and every visit can be viewed as an opportunity to update and complete an adolescent's immunizations.In the past decade, the adolescent immunization schedule has expanded to include 2 doses of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 84 publications
1
46
0
2
Order By: Relevance
“…Later in 2015, ACIP issued a Category B recommendation for MenB vaccination in individuals aged 16‐23 years, with vaccination preferred between the ages of 16 and 18 years . As indicated by the Category B classification, the decision to vaccinate (or not) will be based on the judgment of the healthcare provider and individual patient/family preference following discussion and evaluation of the risks and benefits of MenB vaccination …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Later in 2015, ACIP issued a Category B recommendation for MenB vaccination in individuals aged 16‐23 years, with vaccination preferred between the ages of 16 and 18 years . As indicated by the Category B classification, the decision to vaccinate (or not) will be based on the judgment of the healthcare provider and individual patient/family preference following discussion and evaluation of the risks and benefits of MenB vaccination …”
Section: Resultsmentioning
confidence: 99%
“…Compared with younger children, older adolescents generally have fewer primary care visits and more visits with specialists, who are less focused on vaccination . There are also a number of potential provider‐related barriers to immunization, including knowledge gaps with respect to vaccine indications and recommendations, and poor communication with parents and/or adolescents . Healthcare policies for vaccination may play a key role in overcoming barriers to vaccination, but until those are widespread, those at the point of care (ie healthcare providers) are the ones who must encourage patient vaccination.…”
Section: What Is New and Conclusionmentioning
confidence: 99%
See 2 more Smart Citations
“…These visits are excellent opportunities for providers to encourage patients to receive the HPV immunization because studies have shown that patients are more willing to accept the HPV vaccine when it is viewed as routine or when given with other injections. 33 …”
Section: Commentmentioning
confidence: 99%